2002
DOI: 10.1097/00054725-200211000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inflammatory Bowel Disease on Labor Force Participation: Results of a Population Sampled Case-Control Study

Abstract: IBD has a significant impact on labor force participation that is higher in CD compared with UC and highest in younger and more highly educated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
3
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 10 publications
8
58
3
3
Order By: Relevance
“…The work disability rates of IBD patients range between 1.3% and 34% (45) . The frequent flares requiring hospitalization or surgical intervention often leads to sick leave and disability pensions (2,3,4,6,20,44) , which may be the main reason for the decreased career fulfillment in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work disability rates of IBD patients range between 1.3% and 34% (45) . The frequent flares requiring hospitalization or surgical intervention often leads to sick leave and disability pensions (2,3,4,6,20,44) , which may be the main reason for the decreased career fulfillment in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mean value of the IBDQ-32 was significantly lower among female patients (147. 6 The remaining variables included in our study: age (P = 0.343), duration of IBD (P = 0.314), educational level (P = 0.101), workplace status (P = 0.316), IBD-related hospital admission (P = 0.271), IBD-related surgical procedure (P = 0.271), smoking habits (P = 0.789) and medication (topical aminosalicylates P = 0.462, oral aminosalicylates P = 0.947, steroids P = 0.102, azathioprine P = 0.765 and biological therapeutic P = 0.190) did not show statistically significant differences. The relationship between psychosocial, clinical, and demographic variables and the overall score of IBDQ-32 are shown in Table 3.…”
Section: Determinants Of Quality Of Lifementioning
confidence: 99%
“…13,14 In addition to these direct health costs, another important indirect economic consequence of this chronic illness in an economically productive age-group is the cost attributable to lost work productivity and permanent work disability. [15][16][17][18] Hence, measuring the long-term performance of CD drug therapy in routine clinical care needs to emphasize prevention of these CD-related complications. Evaluation of long-term use of infliximab in the routine clinical setting beyond 1 year and its ability to decrease these CD-related complications has been limited to date.…”
mentioning
confidence: 99%
“…There may be very different employment challenges associated with individual chronic conditions. There have been several recent studies (Bishop, 2002;Begley et al, 2000;Boonen et al, 2002;Gignac et al, 2004;Lacaille & Hogg, 2001;Longobardi et al, 2003;Stang et al,1998) that examined specific chronic physical conditions and associated factors relating to employment. Such research has studied: fibromyalgia, arthritis and rheumatism, diabetes, epilepsy, inflammatory bowel disease, (eg.…”
Section: Chronic Conditions and Employmentmentioning
confidence: 99%
“…Longobardi et al (2003) found evidence in the 1998 Canadian National Population Health Survey of reduced work force participation associated with inflammatory bowel disease within this age group. A Dutch population-based study by Boonen et al (2002) found that work disability related to inflammatory bowel disease was highest among younger and more highly educated respondents compared to the general population.…”
Section: Chronic Conditions and Employmentmentioning
confidence: 99%